A review on chemical mechanism of microalgae flocculation via polymers - Pugazhendhi, Arivalagan (Biotechnol Rep (Amst), 2019)
Industrially, harvesting of the microalgal biomass is a techno-economic tailback, which essentially meant for the algal biomass industry. It is considered energy as well as cost-intensive in view of the fact that the dewatering process during harvesting. In this review chemical reactions involved in the flocculation of microalage biomass via various certain principal organic polymers are focused. Besides, it focuses on natural biopolymers as flocculants to harvest the cultivated microalgae. Commercially, bio-flocculation is suitable and cost-effective in the midst of a range of adopted harvesting techniques and the selection of an appropriate bioflocculant depends on its efficacy on the several microalgae strains like potential biomass fixation, ecological stride and non-perilous nature. The harvesting of toxin free microalgae biomass in large quantity by such flocculants can be considered to be one of the most cost-effective performances towards sustainable biomass recovery.